OBESITY, AN EMERGING EPIDEMIC IN PAKISTAN-A REVIEW OF EVIDENCE - Tanzil, Sana; Jamali, Tanzil (Journal of Ayub Medical College Abbottabad, 2016)
Background: In Pakistan, the disease pattern is facing a huge changeover from acute and communicable diseases to the non-communicable diseases. Moreover, an emerging epidemic of obesity is still under recognized in Pakistan. A detailed review and dissemination of the existing knowledge to determine the extent of burden of obesity can help understand this important public health issue. Methods: A detailed literature review was conducted through PubMed search engines, regarding obesity burden in Pakistan. The original peer reviewed research articles, reports of WHO in English language, non-government organizations reports were included in the review. Obesity AND Pakistan were used as a search terms. Results: Pakistan is suffering from epidemic of obesity, affecting all age groups. Urban population, particularly women shows considerable higher burden of obesity as compared to men and women from rural population. However, among children and adolescents there is variation in prevalence of obesity. Girls from all age groups are predominantly more obese as compared to boys. Most of the studies have estimated child obesity among school going children of different age groups and need careful interpretation. Conclusion:Pakistan is currently suffering from an emerging epidemic of obesity. The rising burden of obesity is widespread among adults (man and women) and children. The burden of obesity is higher among females in all age groups as compare to males. Effective interventions are required at population level to prevent and control this emerging public health issue. Keywords: Obesity; Malnutrition; Epidemic, Pakistan